2022
DOI: 10.3390/polym14051060
|View full text |Cite
|
Sign up to set email alerts
|

Low-Velocity Impact Behavior of Foam Core Sandwich Panels with Inter-Ply and Intra-Ply Carbon/Kevlar/Epoxy Hybrid Face Sheets

Abstract: Sandwich composites are extensively employed in a variety of applications because their bending stiffness affords a greater advantage than composite materials. However, the aspect limiting the application of the sandwich material is its poor impact resistance. Therefore, understanding the impact properties of the sandwich structure will determine the ways in which it can be used under the conditions of impact loading. Sandwich panels with different combinations of carbon/Kevlar woven monolithic face sheets, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It is worth-mentioning that the test specimens underwent drop weight experiment and they were clamped with the four edges to avoid the vibration of the target plate.
Figure 4.Schematic of fractovis plus 7526 drop weight impact tester instruments. 36
…”
Section: Methodsmentioning
confidence: 99%
“…It is worth-mentioning that the test specimens underwent drop weight experiment and they were clamped with the four edges to avoid the vibration of the target plate.
Figure 4.Schematic of fractovis plus 7526 drop weight impact tester instruments. 36
…”
Section: Methodsmentioning
confidence: 99%
“…20 Zhu and Sun 21 divided the low-speed impact response process of a sandwich layer structure into five stages and then established a prediction model for the contact force, impact displacement, and energy absorption properties. Samlal and Santhanakrishnan 22 assessed the impact behavior and the main failure modes of sandwich plates experimentally. Mohammadkhani et al 23 studied the effects of steel wire on the energy absorption performances of sandwich structures from both experimental and numerical perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the impact resistance of the material can be improved by changing the panel material, panel thickness, and foam core size. Sun Ziheng and J. Zhou [13][14][15][16][17][18][19][20][21] studied the impact damage of composite sandwich structures from different stacking methods, different impact methods and different fiber layers, trying to find a structure with high impact resistance. Luo Zhiqiang et al [22][23][24][25] through the study of stitched foam sandwich structure technology, effectively improved the impact resistance of the structure.…”
Section: Introductionmentioning
confidence: 99%